A Self‐Assembling Ligand Switch That Involves Hydroxide Addition to an sp2 Hybridised Phosphorus Atom – A System Allowing OH– Mediated Uptake of [MCl2] (M = Pd, Pt) Centres. Issue 11 (21st February 2019) - Cabon, Yves; Ricard, Louis; Frison, Gilles; Carmichael, Duncan
Abstract : The coordination chemistry of the 1, 1′‐diphosphacobaltocenium salt [Co(η 5 ‐2‐TBS‐3, 4‐Me2 ‐PC4 H)2 ] + BF4 – ( rac ‐1 ) and its derivatives with respect to [MCl2 ] (M = Pd, Pt) centres is presented. Rac ‐1, showing two sp 2 hybridised phosphorus atoms and a positive charge, is stable towards strong electrophiles (PhCH2 Br, MeI), but undergoes attack by hydroxide at phosphorus with subsequent rearrangement to form the neutral conjugate base [Co{η 5 ‐(2‐TBS‐3, 4‐Me2 ‐PC4 H)}{η 4 ‐(1‐O, 1‐H‐2‐TBS‐3, 4‐Me2 ‐PC4 H)}] ( rac ‐2 ). Rac ‐1 undergoes reaction with [MCl2 (PhCN)2 ] (M=Pd, Pt) in damp chloroform to form the P sp2 –P sp3 chelating sec ‐phosphinite complexes [MCl2 {Co{η 5 ‐(2‐TBS‐3, 4‐Me2 ‐PC4 H)}{η 4 ‐(1‐OH‐2‐TBS‐3, 4‐Me2 ‐PC4 H)}}] 4 (M = Pd, Pt), which are also accessible directly, but under more forcing conditions, from rac ‐2 . Computational analysis (M06/def2‐TZVP) indicates that the conjugate base, in the form of its sec ‐phosphinite tautomer rac ‐3, shows significantly stronger bonding to the metal centre than does the parent 1, 1′‐diphosphacobaltocenium salt rac ‐1 . The uptake and subsequent release of a [PtCl2 ] centre as a function of the p H of the reaction medium hints at the potential for employing the rac ‐1 / rac ‐2 ligand acid‐base couple as a p H‐driven coordination switch. Abstract : A reversible Lewis acid conjugate base system involving rac ‐1 has been established. Coordination of rac ‐1 to [PdCl2 ] centres in the presence of moisture provokes the assembly of rac ‐4 . Experimental and DFT studies pertaining to ligand binding are described.